Effect of pressure of vanadium nitride using XRD and DFT. Issue 1 (2nd January 2023) - Xiong, Lun; Huang, Lujun; Liu, Dujin; Ding, Yingchun; Zhang, Junran
ABSTRACT: In this study, synchrotron radiation X-ray diffraction is used to study the equation of state of vanadium nitride in a diamond anvil cell at room temperature. Experimental results reveal the high stability of the cubic structure up to 76 GPa pressure. In addition, the bulk modulus of vanadium nitride derived from XRD data is K 0  = 328.4(2.8) GPa with K 0 ′ = 5.86(0.14). Finally, the high pressure compression behavior is investigated to 80 GPa using density functional theory of first-principle calculations, and the obtained bulk elastic modulus is 316 GPa. Vanadium nitride is not magnetic in the whole pressure range and is metallic. Highlights We have investigated the equation of state of VN under high pressure with silicone oil as the pressure transmitting medium to 76 GPa. It was found that the face-centred cubic structure of VN maintains the maximum pressure of 76 GPa. We have carried out first-principles calculations and obtained the equation of state, band structure, and electronic density of state of VN to 80 GPa.